2021
DOI: 10.3390/ijms22115937
|View full text |Cite
|
Sign up to set email alerts
|

Implications of SGLT Inhibition on Redox Signalling in Atrial Fibrillation

Abstract: Atrial fibrillation (AF) is the most common sustained (atrial) arrhythmia, a considerable global health burden and often associated with heart failure. Perturbations of redox signalling in cardiomyocytes provide a cellular substrate for the manifestation and maintenance of atrial arrhythmias. Several clinical trials have shown that treatment with sodium-glucose linked transporter inhibitors (SGLTi) improves mortality and hospitalisation in heart failure patients independent of the presence of diabetes. Post ho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 156 publications
0
16
0
Order By: Relevance
“…Although available data is insufficient to support the effect of vitamin K in ameliorating prediabetes (the impaired glucose tolerance, fasting blood sugar, fasting serum insulin level would not be restored), the glucose and insulin levels of 2-h post-oral glucose tolerance test could be reduced by stable vitamin K support ( 10 , 30 , 31 ), which indicate that DOACs may not induce the rapid deterioration of prediabetes compared with warfarin. Also, the clinical trials have demonstrated that the new anti-diabetic drug sodium-glucose linked transporter inhibitors (SGLTi) with a beneficial effect on cardiovascular disease ( 32 34 ), regardless if diabetes exists or not ( 34 ). In the aspect of AF, SGLTi can counteract the production of cellular ROS in cardiomyocytes, which may change atrial remodeling and reduce the burden of AF ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although available data is insufficient to support the effect of vitamin K in ameliorating prediabetes (the impaired glucose tolerance, fasting blood sugar, fasting serum insulin level would not be restored), the glucose and insulin levels of 2-h post-oral glucose tolerance test could be reduced by stable vitamin K support ( 10 , 30 , 31 ), which indicate that DOACs may not induce the rapid deterioration of prediabetes compared with warfarin. Also, the clinical trials have demonstrated that the new anti-diabetic drug sodium-glucose linked transporter inhibitors (SGLTi) with a beneficial effect on cardiovascular disease ( 32 34 ), regardless if diabetes exists or not ( 34 ). In the aspect of AF, SGLTi can counteract the production of cellular ROS in cardiomyocytes, which may change atrial remodeling and reduce the burden of AF ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the clinical trials have demonstrated that the new anti-diabetic drug sodium-glucose linked transporter inhibitors (SGLTi) with a beneficial effect on cardiovascular disease ( 32 34 ), regardless if diabetes exists or not ( 34 ). In the aspect of AF, SGLTi can counteract the production of cellular ROS in cardiomyocytes, which may change atrial remodeling and reduce the burden of AF ( 34 ). This suggests that the new anti-diabetic drug SGLTi and new oral anticoagulants DOAC may have similar effects on the prevention of new-onset diabetes during AF treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, AMPK tightly regulates endogenous cardioprotective signaling pathways ( 51 , 52 ). The activation (i.e., phosphorylation) of AMPK mitigates the impaired expression of proteins involved in mitochondrial homeostasis, as well as antioxidant genes ( 53 , 54 ), which influence the increase in mitochondrial biogenesis and the decrease in mitochondrial ROS generation ( 13 ). In addition, AMPK influences the homeostasis of mitochondrial dynamics through phosphorylation of the mitochondrial fission factor ( 13 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress refers to elevated intracellular levels of ROS, either due to excessive ROS generation or reduced ROS scavenging, which results in damage to lipids, proteins, and DNA ( 12 ). Oxidative stress and inflammation contribute to the pathogenesis of AF in patients with DM ( 4 , 13 ). Indeed, previous studies have demonstrated that the reduction of ROS generation reduces AF inducibility in several experimental AF models ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing experimental studies suggest that SGLTi not only attenuates HF but also counteracts cellular ROS production in cardiomyocytes, thereby potentially hampering myocardial remodeling and reducing AF and VF burden. This important feature of SGLT2i is linked to their impact on redox signaling in AF, and this has recently been comprehensively reviewed [133]. SGLT2i also exerts direct antiinflammatory and anti-oxidative effects on resting endothelial cells, and its anti-oxidative effect could be partly mediated by NADPH oxidase inhibition [134].…”
Section: Antiarrhythmic Efficacy Of Sglt2 Inhibitorsmentioning
confidence: 99%